Pengaruh Profesionalisme Dan Kepribadian Terhadap Kinerja Guru - Bahrudi Efendi Damanik; Susiani Susiani; Fitri Rizki; Ika Okta Kirana (Lembaga Pengembangan Kinerja Dosen, 2023)
This research was conducted aiming to determine the effect of professionalism, personality on teacher performance partially and simultaneously. The method used is a survey method with a quantitative approach, namely an approach that uses numbers that are processed through non-parametric statistical analysis in analyzing correlational research results. This research is included in the associative type, which contains a complete picture of the relationship between one variable and another variable, has a linear relationship type, because basically it wants to see the relationship between the independent variables, namely teacher professionalism and personality, with a sample size of 51 people. The conclusion of the research simultaneously that professionalism and personality variables have a positive and significant effect on teacher performance can be seen where the F-count value > F-table (27.672 > 2.790), partially the professionalism variable has a positive and significant effect on teacher performance where the t-count value > t-table (3.295 > 2.000), and partially the personality variable has a positive and significant effect on teacher performance where the value of tcount > ttable (3.884 > 2.000).